Is neurological assessment of the fetus possible? - Prechtl, Heinz F.R; Einspieler, Christa (European journal of obstetrics & gynecology and reproductive biology, 1997)
The possibility to assess the functional condition of the fetal nervous system is of great importance to the obstetrician, since a considerable part of early brain damage is of prenatal origin. Several attempts to develop such a technique are reviewed. In addition, a new method, the qualitative assessment of fetal general movements, is described as a successful tool to obtain reliable data on the fetal brain dysfunction. This new method is robust, non-intrusive and cost-effective. There is also the advantage that the same criteria for the diagnostic assessment can be used for the fetus as well as for the young infant.